PENERAPAN ISAK NO. 35 TERHADAP LAPORAN KEUANGAN MASJID NURUL HAYAT LEWOLANG - Eugenia Hendrini P. Tanan; Asriyanti S. Bali (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2022)
This research is aimed to collect more empirical of ISAK No. 35 related to the Presentation of Financial Statements of Non-profit Oriented Entities at the Nurul Hayat Lewolang Mosque. Data collection techniques used descriptive qualitative methods with interviews, observations and documentation. The study used secondary and primary data. The study resulted in evidence that the financial statements of the Nurul Hayat Lewolang Mosque were not in line with ISAK No. 35. The financial report of the Nurul Hayat Lewolang Mosque which has been adjusted by ISAK No. 35 by classifying transactions, compiling general journals, transferring to ledgers, compiling trial balances. Finally resulted in an accounting process flow in the form of a Statement of Financial Position, Statement of Comprehensive Income, Statement of Changes in Net Assets, and Statement of Cash Flows, as well as Notes to Financial Statements.